2009
DOI: 10.1093/gerona/glp179
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Aging on Human Skeletal Muscle Mitochondrial and Intramyocellular Lipid Ultrastructure

Abstract: The purpose of this study was to determine whether ultrastructural changes in intramyocellular lipid (IMCL) and mitochondria occur with aging. Muscle samples were analyzed from 24 young and 20 old, equally active, individuals for IMCL and mitochondria quantity and size as well as their association. Old men had larger IMCL droplets than all other groups in the total muscle area. Old individuals showed higher IMCL content in the subsarcolemmal area. Young participants had a greater number of mitochondria compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
172
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(192 citation statements)
references
References 40 publications
19
172
1
Order By: Relevance
“…In white muscle, moreover, subsarcolemmal mitochondria were rarely observed, while intermyofibrillar mitochondria appeared highly organised in doublets (Fig. 4c) flanking the Z-lines, as has been seen by others [26]. Despite the scarcity of white muscle subsarcolemmal and intermyofibrillar mitochondria, these, when detected, did not differ in size in the two subcellular regions of lean or obese animals (Fig.…”
Section: Mitochondrial Size and Densitysupporting
confidence: 77%
“…In white muscle, moreover, subsarcolemmal mitochondria were rarely observed, while intermyofibrillar mitochondria appeared highly organised in doublets (Fig. 4c) flanking the Z-lines, as has been seen by others [26]. Despite the scarcity of white muscle subsarcolemmal and intermyofibrillar mitochondria, these, when detected, did not differ in size in the two subcellular regions of lean or obese animals (Fig.…”
Section: Mitochondrial Size and Densitysupporting
confidence: 77%
“…The subcellular localization of mitochondria and the overall 2538 Journal of Cell Science 123 (15) Journal of Cell Science mitochondrial network in multinucleated muscle fibers are tightly controlled by mitochondrion-shaping proteins, and an imbalance in mitochondrial fusion and fission dynamics probably impairs their function and contributes to the age-related loss of muscle. Indeed, it has recently been shown that the expression of Mfn2 and Drp1 genes is reduced in the skeletal muscle of aging individuals (Crane et al, 2010). Furthermore, the role of mitochondrionshaping proteins has recently been investigated in mice with a muscle-specific deficiency in Fis1 and Drp: diminished mitochondrial fission was associated with reduced muscle atrophy and attenuated activation of atrophy-related genes during fasting (Romanello et al, 2010).…”
Section: A Synthesis: Linking Mitochondrial Dynamics and Agingmentioning
confidence: 99%
“…Older adults have larger IMCL droplets, higher content in the subsarcolemmal area, fewer mitochondria, and a lower proportion of IMCL in contact with mitochondria compared with IMCL occurring in young skeletal muscle. These factors likely contribute to agerelated reductions in mitochondrial function and oxidative metabolism [63]. Magnetic resonance spectroscopy studies have shown that IMCL levels vary with insulin sensitivity and obesity, which is a common clinical picture in the older adult, and that inactivity combined with overconsumption of fat can have detrimental effects on muscular insulin sensitivity [64].…”
Section: Aging Skeletal Musclementioning
confidence: 99%